Adult T-Cell Leukemia/Lymphoma With Primary Lacrimal Gland Involvement. Issue 1 (January 2018) - Sabundayo, Maria Suzanne; Takahashi, Yasuhiro; Kakizaki, Hirohiko
Abstract : A 69-year-old Japanese male presented with a 3-month history of bilateral ptosis with lacrimal gland bulge. He came from western Japan, an area endemic for human T-lymphotropic virus Type 1 infection. Physical examination and imaging revealed bilaterally enlarged lacrimal glands. Hematologic testing, biopsy with histopathology, and immunohistochemistry were all consistent with adult T-cell leukemia/lymphoma. Abstract : This is the first case of adult T-cell leukemia/lymphoma with primary involvement of the lacrimal gland that clinically presented as ptosis.